Computer-assisted, template-guided immediate implant placement and loading in the mandible: a case report - Thomas Spielau; Uli Hauschild; Joannis Katsoulis (BMC, 2019)
Abstract Background Computer-assisted implant planning has become an important diagnostic and therapeutic tool in modern dentistry. This case report emphasizes the possibilities in modern implantology combining virtual implant planning, guided surgery with tooth and implant supported templates, immediate implant placement and loading. Case presentation A straight forward approach was followed for the mandible presenting with hopeless lower incisors. Diagnosis, decision making and treatment approach were based on clinical findings and detailed virtual three-dimensional implant planning. Extractions of the hopeless mandibular incisors, immediate and guided implant placement of six standard implants, and immediate loading with a provisional fixed dental prosthesis (FDP) were performed fulfilling patient's functional and esthetic demands. The final computer assisted design / computer assisted manufacturing (CAD/CAM) FDP with a titanium framework and composite veneering was delivered after 6 months. At the 1-year recall the FDP was free of technical complications. Stable bony conditions and a healthy peri-implant mucosa could be observed. Conclusions Computer assisted implantology including three-dimensional virtual implant planning, guided surgery, and CAD/CAM fabrication of provisional and final reconstructions allowed for a concise treatment workflow with predictable esthetic and functional outcomes in this mandibular full-arch case. The combination of immediate implant placement and immediate loading was considerably more complex and required a high level of organization between implantologist, technician and patient. After the usage of a first tooth-supported surgical template with subsequent extraction of the supporting teeth, a second surgical template stabilized on the previously inserted implants helped to transfer the planned implant position in the extraction sites with a guided approach.